Promoting the construction of intelligent knowledge with the help of various methods of cognitively activating instruction - Schumacher, Ralph; Stern, Elsbeth (Frontiers in Education, 2023)
How can we promote the construction of intelligent knowledge that facilitates the transfer of knowledge to new situations? This article gives an overview of the current state of empirical research on methods of cognitively activating teaching that promote conceptual change and flexible application of knowledge in new situations. “Cognitively activating” means that these methods promote the active construction of knowledge by facilitating a better understanding of the problem at hand, by activating relevant prior knowledge, and by fostering a better awareness of the limits of one’s own knowledge. Six methods that have each proven successful in boosting learners’ conceptual understanding in experimental studies are presented in this article.